Increased frequency of CD4⁺ CD25⁺ regulatory T cells in the cerebrospinal fluid but not in the blood of multiple sclerosis patients - Feger, U; Luther, C; Poeschel, S; Melms, A; Tolosa, E; Wiendl, H (Clinical and experimental immunology, 2007)
Naturally occurring CD4⁺ CD25⁺ regulatory T cells (nTreg) play a major role in controlling autoimmunity by suppressing self-reactive T cells. Multiple sclerosis (MS) is an inflammatory demyelinating disorder of the central nervous system (CNS), where T cells play a key role in orchestrating tissue damage. While CD4⁺ CD25⁺ nTreg have been investigated in peripheral blood from MS patients, little is known about their presence and possible function within the target organ, the CNS. In order to study whether these cells are present in the cerebrospinal fluid (CSF) under pathological conditions, we have analysed the frequency of CD4⁺ CD25⁺ nTreg in peripheral blood and CSF from MS patients (n = 14), patients with other neurological disorders (OND; n = 9) and compared peripheral levels with healthy controls (n = 40). We found that the frequency of CD4⁺ CD25⁺ forkhead transcription factor 3 (FOXP3)⁺ nTreg was significantly elevated in the CSF from MS patients (mean CSF = 4·05 ± 1·54% versus mean peripheral blood = 2·93 ± 0·94%) but not from patients with other neurological disorders (mean CSF = 3·78 ± 1·26% versus mean peripheral blood = 3·74 ± 1·4%). The frequency of nTreg in the periphery did not differ between MS patients and healthy donors; however, nTreg from MS patients showed reduced suppressive capacity.